„Nowy” gródek późnośredniowieczny w rejonie jezior bnińskich (Błażejewo, gm. Kórnik, woj. wielkopolskie) - Fogel, Jerzy; Sikorski, Andrzej; Jasiewicz, Jarosław; Łosińska, Alina (Folia Praehistorica Posnaniensia, 2018)
The document from 1422, published in Codex Diplomatics Maioris Poloniae (volume VIII, 1989, No. 935), refers to a fortified mansion from Błażejewo at the Bnin Lake, located about 25 km SE from Poznań. The article presents results of archaeological and geological search of this construction that was undertaken in the year 2000. It was further confronted with other written sources referring to medieval history of two Wielkopolska magnate’s houses: Grzymała and Łodzia-Bniński. The article is an important contribution to the recognition of the late medieval fortified architecture in the Wielkopolska region.